MRGPRX2 sensing of cationic compounds—A bridge between nociception and skin diseases?. Issue 2 (17th November 2020) - Corbière, Auriane; Loste, Alexia; Gaudenzio, Nicolas
Abstract: Mast cells are innate immune cells located at many barrier sites in the body and known to protect the host against environmental threats and to be involved in allergic diseases. More recently, new studies have investigated their roles in the regulation of skin inflammation and transmission of pain and itch sensations. Mast cell signalling through the Mas‐related G protein‐coupled receptor (MRGPR) X2 or its mouse orthologue MRGPRB2 has been reported to be one of the major mechanism by which mast cell can regulate such processes. MRGPRX2 and MRGPRB2 can induce mast cell degranulation upon binding to a broad panel of cationic molecules such as neuropeptides, bacteria‐derived quorum sensing molecules, venom peptides, host defense peptides and, unfortunately, various FDA‐approved drugs. Upon activation, mast cells release granule‐associated proteases, lipids and multiple cytokines that can modulate vascular permeability, immune cells recruitment and activation status of tissue‐projecting nociceptive sensory neurons (ie nociceptors). Here, we discuss the modality of MRGPRX2‐dependent mast cell activation and its different consequences on the patterns of skin inflammation and associated diseases. We notably emphasize how MRGPRX2‐dependent skin mast cell activation might trigger various pathological traits such as pruritus, pain and inflammation and therefore become a potential therapeutic target for inflammatory pain, itch, atopic dermatitis and drugs‐induced injection site reactions.